Dirac Fermion Kinetics in 3D Curved Graphene. Issue 48 (28th October 2020) - Tanabe, Yoichi; Ito, Yoshikazu; Sugawara, Katsuaki; Koshino, Mikito; Kimura, Shojiro; Naito, Tomoya; Johnson, Isaac; Takahashi, Takashi; Chen, Mingwei
Abstract: 3D integration of graphene has attracted attention for realizing carbon‐based electronic devices. While the 3D integration can amplify various excellent properties of graphene, the influence of 3D curved surfaces on the fundamental physical properties of graphene has not been clarified. The electronic properties of 3D nanoporous graphene with a curvature radius down to 25–50 nm are systematically investigated and the ambipolar electronic states of Dirac fermions are essentially preserved in the 3D graphene nanoarchitectures, while the 3D curvature can effectively suppress the slope of the linear density of states of Dirac fermion near the Fermi level are demonstrated. Importantly, the 3D curvature can be utilized to tune the back‐scattering‐suppressed electrical transport of Dirac fermions and enhance both electron localization and electron–electron interaction. As a result, nanoscale curvature provides a new degree of freedom to manipulate 3D graphene electrical properties, which may pave a new way to design new 3D graphene devices with preserved 2D electronic properties and novel functionalities. Abstract : 3D curved graphene with a wide range of curvature radii from 25 to 1000 nm demonstrates that nanoscale curvature is a new degree of freedom to tune the transport properties of graphene by manipulating 2D electron kinetics on 3D curved surfaces.